2016
DOI: 10.1016/j.mjafi.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of forearm fractures using a combination of haematoma block and intravenous regional anaesthesia

Abstract: m e d i c a l j o u r n a l a r m e d f o r c e s i n d i a 7 2 ( 2 0 1 6 ) 2 4 7 -2 5Methods: An observational case series was designed with the hypothesis that a combination of HB and IVRA would overcome the aforementioned drawbacks. A standardized protocol was followed for HB with 0.1 ml/kg of 0.5% bupivacaine preceding the conduct of IVRA, which permitted adequate exsanguination of the extremity (using compression bandage). For IVRA, 0.5% lignocaine at 3 mg/kg was used with an electro-pneumatic tourniquet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Several methods of anaesthesia are proposed for closed reduction, among them is, intravenous regional anaesthesia (IVRA)—currently recommended by The National Institute for Health and Care Excellence guidelines 8,9 . Studies have shown that the anaesthesia method influences pain perception and muscle relaxation during closed reduction, consequently affecting the quality of reduction and a number of attempts 10–12 . Current methods of anaesthesia used for closed reduction of DRFs may be insufficient regarding pain relief and muscle relaxation, potentially compromising the reduction quality and patient satisfaction 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods of anaesthesia are proposed for closed reduction, among them is, intravenous regional anaesthesia (IVRA)—currently recommended by The National Institute for Health and Care Excellence guidelines 8,9 . Studies have shown that the anaesthesia method influences pain perception and muscle relaxation during closed reduction, consequently affecting the quality of reduction and a number of attempts 10–12 . Current methods of anaesthesia used for closed reduction of DRFs may be insufficient regarding pain relief and muscle relaxation, potentially compromising the reduction quality and patient satisfaction 13 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies have shown that the anaesthesia method influences pain perception and muscle relaxation during closed reduction, consequently affecting the quality of reduction and a number of attempts. [10][11][12] Current methods of anaesthesia used for closed reduction of DRFs may be insufficient regarding pain relief and muscle relaxation, potentially compromising the reduction quality and patient satisfaction. 13 Peripheral nerve blocks (PNBs) can provide complete afferent and efferent blockade, are well-established for upper extremity surgery and have a good safety profile.…”
mentioning
confidence: 99%
“…Most surgeries at the wrist and forearm are performed using a tourniquet to minimize blood loss [1] and are carried upon under general anesthesia [2], local infiltration [3], brachial plexus blocks [2] or intravenous regional anesthesia (IVRA) [4]. IVRA is an effective method of providing anesthesia for extremity surgery, with published success rates ranging from 94% to 98% [5]. Despite of the settled efficacy of IVRA, it may be associated with serious complications related to local anesthetic (LA) toxicity that may be occurred secondary to LA leak [6], accidental tourniquet release or rapid tourniquet deflation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous regional anaesthesia (IVRA) which was firstly described by August Bier in 1902 [2] is used successfully as a sole technique for upper limb surgeries [3]. It is a reliable, simple, cost-effective, and widely accepted technique of regional anaesthesia [1].…”
Section: Introductionmentioning
confidence: 99%